2021
DOI: 10.1055/s-0041-1731789
|View full text |Cite
|
Sign up to set email alerts
|

A Baby at All Costs? Exploring the Use and Provision of Unproven Adjuvant Treatments in the Context of IVF

Abstract: The year 2018 marked 40 years since the birth of Louise Brown, the first baby born as a result of pioneering in vitro fertilization (IVF) treatment. Since then, advances have seen a wide range of reproductive technologies emerge into clinical practice, including adjuvant treatments often referred to as IVF “add-ons.” However, these “optional extras” have faced growing criticism, especially when they have often come at additional financial cost to the patient and have little evidence supporting their efficacy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Since pregnancy rates have generally plateaued following decades of improvement of ART, physicians often tend to use various add-ons or adjuvants in attempts to improve the factors relevant to implantation, even though robust evidence for these adjuvant therapies remained limited ( 2 ). Despite the criticism of unproven efficacy and additional resource consumption ( 3 ), the use of add-ons/adjuvants in ART is widespread. It is estimated that 65% of women undergoing IVF in the U.K. used one or more add-ons in 2021 ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since pregnancy rates have generally plateaued following decades of improvement of ART, physicians often tend to use various add-ons or adjuvants in attempts to improve the factors relevant to implantation, even though robust evidence for these adjuvant therapies remained limited ( 2 ). Despite the criticism of unproven efficacy and additional resource consumption ( 3 ), the use of add-ons/adjuvants in ART is widespread. It is estimated that 65% of women undergoing IVF in the U.K. used one or more add-ons in 2021 ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…A national survey showed that the median number of add-ons the patients took as part of their treatment was two ( 5 ). Sometimes, the motives for using adjuvants in ART treatments go further than technical issues ( 3 ). Driven by complex motives, such as pursuing solutions to uncertainty, combinations of adjuvants that are supposed to be helpful are used in the same cycle.…”
Section: Introductionmentioning
confidence: 99%